Consciousness and the natural method - Flanagan, Owen (Neuropsychologia, 1995)
‘Consciousness’ is a superordinate term for a heterogeneous array of mental state types. The types share the property of ‘being experienced’ or ‘being experiences’—‘of there being something that it is like for the subject to be in one of these states.’ I propose that we can only build a theory of consciousness by deploying ‘the natural method’ of coordinating all relevant informational resources at once, especially phenomenology, cognitive science, neuroscience and evolutionary biology. I'll provide two examples of the natural method in action in mental domains where an adaptationist evolutionary account seems plausible: (i) visual awareness and (ii) conscious event memory. Then I will discuss a case, (iii), dreaming, where I think no adaptationist evolutionary account exists. Beyond whatever interest the particular cases have, the examination will show why I think that a theory of mind, and the role conscious mentation plays in it, will need to be built domain-by-domain with no a priori expectation that there will be a unified account of the causal role or evolutionary history of different domains and competences.